Effect of Training on Employee Performance: Investigating Indian Banking Sector - Wadhwa, Shilpa; Kumar, Manish (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959882);" role="presentation">Most of the banks in India and all around the world are influenced by training and development practices of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912245);" role="presentation">employees in achieving the organ<span dir="ltr" style="left: calc(var(–scale-factor)*207.53px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908198);" role="presentation">izational objectives. There has been a requirement for banks to understand the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960221);" role="presentation">role of training and development to attain high performance. <span dir="ltr" style="left: calc(var(–scale-factor)*329.47px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960326);" role="presentation">The purpose of this paper is to investigate the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953492);" role="presentation">effect of Training as one of the Talent Management practices on Empl<span dir="ltr" style="left: calc(var(–scale-factor)*364.39px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930192);" role="presentation">oyee Performance in the Indian banks. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922183);" role="presentation">The study has outlined two research objectives: First, to develop an understanding about the implementation of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976461);" role="presentation">Training in public and private sector banks in India and second to <span dir="ltr" style="left: calc(var(–scale-factor)*356.23px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.97131);" role="presentation">explore the relationship of Training and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949429);" role="presentation">Development with Employee Performance in the banking sector in India. The study adopted a survey of 550 <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911372);" role="presentation">bank employees through <span dir="ltr" style="left: calc(var(–scale-factor)*174.74px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93367);" role="presentation">self-<span dir="ltr" style="left: calc(var(–scale-factor)*192.65px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902914);" role="presentation">administered <span dir="ltr" style="left: calc(var(–scale-factor)*247.37px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944121);" role="presentation">questionnaire which results in the collection of primary data for the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*413.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.859778);" role="presentation">research. <span dir="ltr" style="left: calc(var(–scale-factor)*111.14px); top: calc(var(–scale-factor)*413.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941812);" role="presentation">The study finds that <span dir="ltr" style="left: calc(var(–scale-factor)*196.61px); top: calc(var(–scale-factor)*413.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*212.09px); top: calc(var(–scale-factor)*413.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974581);" role="presentation">Train<span dir="ltr" style="left: calc(var(–scale-factor)*233.81px); top: calc(var(–scale-factor)*413.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952871);" role="presentation">ing and Development is the influencing force for work performance in <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*427.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974954);" role="presentation">banks which signifies that employees in this sector are willing to learn and update themselves. As per the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915984);" role="presentation">regression summary, the value of Adjusted R2 <span dir="ltr" style="left: calc(var(–scale-factor)*258.65px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912245);" role="presentation">is 0.676 which shows that employee <span dir="ltr" style="left: calc(var(–scale-factor)*406.99px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910622);" role="presentation">performance was affected by <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*453.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929024);" role="presentation">training and development practice. This implies that, there was a variation of 67.6% on employee performance <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*466.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924131);" role="presentation">with training and development.